1993
DOI: 10.1111/j.1600-0447.1993.tb03438.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental rearing and intimate relations in women's depression

Abstract: Bowlby has suggested that attachment behavior is not restricted to early childhood but can remain valid through the life span. This study was designed to test whether recall of parental rearing (Parental Bonding Instrument) and perception of marital relationship (Dyadic Adjustment Scale) is significantly different between 2 groups of women: one with non-bipolar depressive disorder (DSM-III-R) compared with another (control) of healthy women from a primary practice setting. We also examined the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Evidence for actor effects is consistent with studies that have demonstrated within-person associations between psychopathology and marital satisfaction in treatment-seeking (e.g., Chambless et al, 2002;Vega et al, 1993) and community (Goering et al, 1996;Whisman, 1999) samples. Evidence for partner effects was more mixed, in that a person's own depression score was significantly associated with lower marital satisfaction in his or her partner.…”
Section: Discussionsupporting
confidence: 72%
“…Evidence for actor effects is consistent with studies that have demonstrated within-person associations between psychopathology and marital satisfaction in treatment-seeking (e.g., Chambless et al, 2002;Vega et al, 1993) and community (Goering et al, 1996;Whisman, 1999) samples. Evidence for partner effects was more mixed, in that a person's own depression score was significantly associated with lower marital satisfaction in his or her partner.…”
Section: Discussionsupporting
confidence: 72%
“…189 (87.9%) of the respondents who were satisfied with their marriage had a GHQ score of less than 4 as compared to 28 (60%) with a score of more than 4 who were dissatisfied with their marriage. In other words the supposed absence of psychological dysfunction enhances marital satisfaction and conversely the presence of psychological dysfunction will result in marital dissatisfaction, this supports the "actor effect" perspective [20][21][22][23][24][25]. However, in agreement with Whisman, Uebelacker & Weinstock [36] unless data from both individuals are included, one cannot determine to what extent the observed associations between measures of psychopathology and marital satisfaction are due to one partner's own mental health versus the other partner's mental health.…”
Section: Discussionmentioning
confidence: 69%
“…The positively worded items were 1, 3,5,8,9,11,13,16,17,19,20,21,23. The questionnaire adopts a Likert scoring scale which ranges from rarely or none of the time (1) A little or none of the time (2) Sometimes (3) A good part of the time (4) and Most of the time (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the realities faced by college students are more complicated than those faced by college students a few years ago (Vega, Bayon, Franco, Canas, Graell, & Salvador, 1993). The stress and challenge from academic, employment, economic and emotional aspects have caused worrisome problems in their mental health.…”
Section: The Main Problems In the Psychological Health Educationmentioning
confidence: 99%